Gender-responsive public financial management: The Indian chronology of gender budgeting - Lekha Chakraborty (Levy Economics Institute of Bard College, 2024)
Gender budgeting is a public financial management (PFM) tool, used to ensure accountability mechanisms. The analysis of "process" indicators of gender-responsive PFM (GRPFM) reveals that India has been successful in integrating a gender lens within the budget cycle, including in the financial planning and allocation, and in effective implementation. However, a legally mandated GRPFM would be crucial for the sustained impact of gender budgeting on gender equality outcomes. The empirical analysis of the link between GRPFM and gender equality outcomes showed that flexibility of finances is crucial for a government to implement GRPFM. The unconditional fiscal transfers have relatively more impact on gender equality outcomes than conditional transfers. The plausible mechanism through which unconditional tax transfers impact gender equality outcomes lies in the flexibility of use of tax transfers by the subnational governments in prioritizing their gender-related commitments. This inference has policy implications for the 16th Finance Commission.
Keywords: H3; H5; H8; 330; Public Financial Management; Gender Budgeting; Fiscal Innovation; Accountability